2018
DOI: 10.1111/ina.12453
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure to polycyclic aromatic hydrocarbons, kitchen ventilation, fractional exhaled nitric oxide, and risk of diabetes among Chinese females

Abstract: Diabetes is related to exposure to polycyclic aromatic hydrocarbons (PAHs), inflammation in the body, and housing characters. However, associations of urinary monohydroxy-PAHs (OH-PAHs) or fractional exhaled nitric oxide (FeNO) with diabetes risk in relation to housing characters are unclear. In this study, 2645 individuals were drawn from the baseline survey of the Wuhan-Zhuhai Cohort Study. Associations of diabetes with urinary OH-PAHs or FeNO among cooking participants were estimated using logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 59 publications
(69 reference statements)
1
17
0
Order By: Relevance
“…This discrepancy might be partly due to the lower urinary levels of 1-OHP and 1-OHPhe in Korea than in other countries. 11 14 , 16 18 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might be partly due to the lower urinary levels of 1-OHP and 1-OHPhe in Korea than in other countries. 11 14 , 16 18 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…Cooking fume exposure has been found to be related with many chronic diseases such as lung cancer, cardiovascular disease and diabetes. [8][9][10] Previous animal studies also found that carcinogens contained in cigarette smoke, which can also be found in cooking oil fume, might accelerate fat deposition in liver. [14] However, clinical data on the association between environmental exposure to cooking oil fume and fatty liver disease is limited.…”
Section: Discussionmentioning
confidence: 99%
“…found that environmental exposure to cooking oil fume is also associated with diabetes. [10] However, few studies has analyzed the association between cooking oil fume and fatty liver although Ames test and the SOS chromotest have found that cooking oil fume contains genotoxicity which related to fatty deposition [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In China alone, the number of people exposed to COFs in 2018 has reached to 240 million and most of whom were middle-aged women . Women exposed to COFs are at higher risk for chronic bronchitis, for pregnant women, such exposure can also affect the fetus and increase the risks of adverse birth outcomes (Hou et al 2018;Vavalà et al 2014;Zhu et al 2019) . The occurrence of these diseases may be related to cytotoxic damage caused by COFs, it has been reported that the use of ventilation equipment can reduce the risk of cardiopulmonary death to 40% within ve years (Ma et al 2021).…”
Section: Introductionmentioning
confidence: 99%